Instagram Promotion Effectiveness and the Mediating Role of Brand Awareness in Influencing Consumer Purchase Decisions at a Coffee Business - Ellecia Pricillia Siahaan; Sri Tjondro Winarno; Taufik Setyadi (Jurnal Ilmiah Membangun Desa dan Pertanian, 2025)
Indonesia has experienced significant growth in both coffee production and consumption, driving the development of local coffee businesses. Amid increasing competition, Instagram has become a primary platform for promotional strategies due to its visual strength and broad reach. This study aims to analyze the influence of Instagram promotion effectiveness on consumer purchase decisions, with brand awareness as a mediating variable. Promotion effectiveness is measured using the Stimulus-Organism-Response (SOR) Model, which encompasses stimulus (content quality), organism (attention, comprehension, and acceptance), and response (interaction and participation). The study was conducted at Sumber Wandhe Coffee Lab, Jombang, East Java, from January 2025, utilizing field observations and interviews supported by Google Forms, and employing a quantitative approach. A total of 100 respondents, out of 4,000 followers of Sumber Wandhe Coffee Lab on Instagram, were selected using purposive sampling. Data were collected via an online questionnaire and analyzed using Structural Equation Modeling Partial Least Squares (SEM-PLS) through WarpPLS 8.0. This study examined the relationship among three main variables: Instagram promotion effectiveness, brand awareness, and purchase decision. The results show that Instagram promotional content received high average scores in stimulus (4.23), organism (4.24), and response (4.15), with an overall effectiveness score of 4.20. The outer Model met the validity and reliability criteria. The inner model analysis revealed a significant direct effect of Instagram promotion on brand awareness (β = 0.83, p < 0.01) and a significant effect of brand awareness on the purchase decision (β = 0.62, p < 0.01). The indirect effect of promotion on purchase decision through brand awareness was more substantial than the direct path. These findings confirm that brand awareness serves as a key mediator linking the effectiveness of Instagram promotion to consumer purchasing behavior.